GIS-Based Multi-Criteria Land Suitability Analysis for Five Tropical Forage Legumes in Highland Agroecosystems - Qamara, Cori; Yuzaria, Dwi; Madarisa, Fuad; Budiarsa, Anugrah Aditya (Fakultas Peternakan, Universitas Padjadjaran, 2025)
In this study, GIS-based land suitability analysis is used to optimize the cultivation of forage for goat production in Limapuluh Kota Regency, West Sumatra. We assessed five important forages—cassava, Calliandra calothyrsus, Gliricidia sepium, Sesbania grandiflora, and Leucaena leucocephala—by incorporating a multi-criteria evaluation (including slope, soil characteristics, and climate conditions). Results show clear agroecological niches: cassava flourishes extensively, even on marginal lands, C. calothyrus and G. sepium need specific adaptations to soil and climate, Sesbania grandiflora excels as a high-protein choice in various zones, whereas Leucaena leucocephala requires strict geographic targeting. Processing protocols (sun-drying, co-feeding) and species-specific rehabilitation were implemented to address critical constraints such as soil acidity, elevation, and anti-nutritional compounds (tannins, mimosine). The study creates a new suitability classification framework that allows for precise zoning of forage development. The main recommendations are to focus on Sesbania grandiflora in central valleys, cassava on slopes at risk of erosion, and Gliricidia sepium in lowland regions, while limiting Leucaena leucocephala to areas with optimal microclimates. This method strengthens the resilience of smallholders by cutting down feed expenses, boosting goat productivity, and promoting sustainable land use in accordance with SDGs 2 (Zero Hunger) and 13 (Climate Action). Policy integration includes spatial planning maps along with targeted subsidy schemes for acid-tolerant legumes.